Low-Level Laser Action on Orthodontically Induced Root Resorption: Histological and Histomorphometric Evaluation - Vasconcelos, Eliziane Cossetin; Henriques, Jose Fernando Castanha; Sousa, Marinês Vieira Silva; Oliveira, Rodrigo Cardoso de; Consolaro, Alberto; Pinzan, Arnaldo; Henriques, Fernanda Pinelli; Bronfman, Caroline Nemetz (Journal of Lasers in Medical Sciences, 2016)
Introduction: Studies have been conducted to develop a means of preventing, controlling or reducing orthodontically induced root resorption. Phototherapy has demonstrated effectiveness as an anti-inlammatory and, considering the inlammatory origin of this pathology, this study evaluated the effects of laser on root resorption. Methods: The research was conducted among 54 80-day-old male Wistar rats, with weights of 280 ± 40 g. Phototherapy consisted of a diode laser (Ga-Al-As), calibrated with a wavelength of 808 nm, an output power of 100 mW, 2.1 J or 96 J of energy and area of 0.0028 cm2. The application was continuous, punctual and with contact. The left irst maxillary molar was moved by a super-elastic closed spring with a pre-calibrated and constant force of 25 g. The specimens were irradiated every 48 hours, totaling three or six times, depending on the group to which they belonged. Euthanasia was made in the 7th or 10th day after the onset of movement. The histological and histomorphometric examination was performed with sections of 6 μm stained with hematoxylin and eosin (H&E). Results: Considering the dosimetry studied, when compared the subgroups with the same time of movement, 7 or 10 days, the low-level laser (LLL) has no statistically signiicant effect on the root resorption. As expected, differences were found between groups with different time of movement. Conclusion: Based on the result, this dosimetry does not seem to be clinically recommended to avoid or reduce inlammatory root resorption, but it also does not induce any root surface alteration.